Effects of alpha-adrenoceptor agonists on cardiac function and blood pressure in rats - LI Qian; QIAN Jia-qing (Acta Pharmacologica Sinica, 2016)
In rat working hearts, alpha 1-adrenoceptor agonist phenylephrine increased LVP, +/- dP/dtmax, ABF and HR in the presence of propranolol. But alpha 2-adrenoceptor agonist B-HT 920 was ineffective. The changes induced by phenylephrine were antagonized by prazosin. In normotensive pithed rats, iv methoxamine dose-dependently increased LVP, +/- dP/dtmax, LVEDP, SAP and DAP. The changes in haemodynamics elicited by iv methoxamine were also antagonized by pretreatment with prazosin, and were attenuated by nifedipine (1 mg/kg, ia). In these two experiments, the increase in HR developed more slowly. The results suggest that postjunctional alpha 1-adrenoceptors, which exist in rat myocardium, produce a positive inotropic effect, which is possibly dependent on influx of extracellular calcium. Postjunctional alpha 2-adrenoceptors-mediated effects were not found in rat myocardium in our functional studies.